Sustainable Development of Rainfed Agricultural Watershed–As Long Term Integrated Land Management System - Hazra, C.R.; Singh, D.P. (Journal of Soil and Water Conservation, 2022)
The Tejpura watershed covering an area of 775.7 hectare is located at east of Jhansi city in Uttar Pradesh. This watershed was treated with an integrated watershed management plan by 1986-87. An earlier report on this project implementation providing bench mark data, changes in land uses, improved moisture condition, higher yields, income etc. as on 1987 appeared in this journal vide vol. 31 (3+4), 1987. After 5 years there has been further increas: in many of the benefits. This provides a pointer that long term and sustainable dividends increases over a few years for which integrated watershed manage- ment and specially, the foundation soil and water conservation treatment that create durable assets, are necessary. An exhaustive account of total benefits is being presented in this paper. The latest scenario reveals that with soil and water conservation measures like contour/submergence cum field blinding in 584 hectares, diversion channel on foot hills of 1657 metre in length, gully plugging on 64 hectares, field drainage system etc. had helped in lowering soil loss from 18.5 tonnes per hectare to 5.4 tonnes per hectare and run off water loss from 75 per cent to 35 per cent and brought back 127 (125) hectare degraded wasteland under cultivation. All these measures and improved prac- tices resulted in increased cropping intensity from 83 per cent to 206 (156) per cent, irrigated area from about 4.6 per cent to 92 (69) per cent and spectacular increase in crop productivity and family income by 9 times (2-4 times) as com- pared to the pre-treatment period . The benefit-cost ratio of the programme stands at 3.8. The rise in watertable in seasons varied from 4 to 7 rn (3 to 7 ni) and with increased recharge irrigation could be given for 10 to 14 hours at a stretch against 2 to 3 hours as was initially possible. About 55 ha could be put to summer cultivation and of vegetables against none. Mandays employment generated also increased front 41515 in 1983-84 to 1,27,200 in 1990-91, while for the bullock days rise was from 30, 590 to 92,260. There has been 3.5 times enrichment in organic matters, significant rise in available nitrogen and phosphorous while soil reaction and bulk density declined which confirmed improvement in physical and chemical environment of soil. The results indicate that longterm benefits are considerable for soil and water conservatioglwatershed management. Evaluation and investment decision should consider this.